Wyrazić Niewyrażalne - karmelitańskie pieśni o miłości Bożej - Kaczor, Katarzyna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2005)
Carmelitan poetry from XVII and XV1I1 centuries, undertook the subject of the love of the God, presents the influences of Spanish mysticism as well the erotic symbolism of The Sonn Above Song. The love, presented by anonymous authors, was compared to the fire of which the flame makes in the object of the love the qualm and faint, the gladness and suffering at once. Carmelitan authors used the metaphors of heart pierced by arrow - of the motif functioned already in antique, next taken over by church fathers (Orygenes, St. Augustin), and then by the great Christian mystics (St. Teresa of Avila and St. John of the Cross). Polish nuns also described ecstasy’s experiences, characteristics by “suspension of the senses,” and by combination of delight and pain simultaneously. They also appealed to the Ecstasy of St. Teresa which illustrated her wound of the love. This style must incarnate spirit. Therefore, carmelitan authors utilized the metaphors of love and sensual stylistic figures. The oxymoron, paradox and hyperbole are figures necessary to the articulation of the love between God and soul, because over simple words it is difficult to express. The sensual stylistic figures were of used to transposition the mysteries of God’s love and reflected relations between human beings and God, presented by - consolidated in receiving conscience the formulas of the language of love. The love is a unity of two complementary parts. This greatest idea wanted to present the language of love and the semantics of passion in poetry of Polish Carmclitans.